2019
DOI: 10.1111/jdi.12984
|View full text |Cite
|
Sign up to set email alerts
|

Basal insulin therapy: Unmet medical needs in Asia and the new insulin glargine in diabetes treatment

Abstract: Diabetes remains a global epidemic and a tremendous health challenge, especially in the Asian population. Dramatic increases in the prevalence of diabetes across different countries or areas in Asia have been reported in recent epidemiological studies. Although clinical guidelines have strengthened appropriate antihyperglycemic medications and lifestyle modifications for optimal diabetes management, inadequate glycemic control still occurs in many patients with an increased risk of developing microvascular and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 91 publications
0
18
0
Order By: Relevance
“…Fear of hypoglycaemia is a barrier to insulin initiation and optimal titration in insulin‐naïve people with T2D . Delay in insulin initiation, suboptimal titration and poor glucose control are issues in the treatment of diabetes in Asia as in other regions . The ORBIT real‐world evidence study showed that ~50% of patients did not have their insulin dose up‐titrated within the first 3 months after starting insulin therapy .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fear of hypoglycaemia is a barrier to insulin initiation and optimal titration in insulin‐naïve people with T2D . Delay in insulin initiation, suboptimal titration and poor glucose control are issues in the treatment of diabetes in Asia as in other regions . The ORBIT real‐world evidence study showed that ~50% of patients did not have their insulin dose up‐titrated within the first 3 months after starting insulin therapy .…”
Section: Discussionmentioning
confidence: 99%
“…29 Delay in insulin initiation, suboptimal titration and poor glucose control are issues in the treatment of diabetes in Asia as in other regions. 11 The ORBIT real-world evidence study showed that 50% of patients did not have their insulin dose up-titrated within the first 3 months after starting insulin therapy. 12 Early glycaemic control increases the likelihood of achieving targets in the longer term, 28 and promotes improved glycaemic outcomes in the longer term.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 We reported that only 10% of patients were treated with a basal-bolus regimen, probably for reasons of patients' acceptability to multiple injections, patients' fear of hypoglycaemia, lack of support systems, and high treatment costs, especially if the treatment is paid out-of-pocket. [27][28][29] The high treatment cost is in part due to the complexity of pricing, procurement, and supply chain of insulin. 28 F I G U R E 3 Modifying effects of gender, young-onset diabetes (YOD), and diabetic kidney disease (DKD) at baseline on the impact of intensive insulin regimens in the entire cohort For each subgroup, the respective reference groups were: premixed -DKD -; basal-bolus -, YOD -; and basal-bolus -, women.…”
Section: F I G U R E 1 Multivariable Linear Regression Analyses Of Thmentioning
confidence: 99%
“…However, existing evidence has consistently reported a similar efficacy in HbA1c reduction, but with a lower risk of hypoglycaemia with the use of analogues insulin compared to human insulin. 29 Last, we acknowledge limitations inherent in crosssectional surveys that precluded causal inference.…”
Section: F I G U R E 1 Multivariable Linear Regression Analyses Of Thmentioning
confidence: 99%